Lung–infiltrating T helper 17 cells as the major source of interleukin-17A production during pulmonary Cryptococcus neoformans infection - Movahed, Elaheh; Cheok, Yi Ying; Tan, Grace Min Yi; Lee, Chalystha Yie Qin; Cheong, Heng Choon; Velayuthan, Rukumani Devi; Tay, Sun Tee; Chong, Pei Pei; Wong, Won Fen; Looi, Chung Yeng (BMC, 2018)
Background: IL-17A has emerged as a key player in the pathologies of inflammation, autoimmune disease, and immunity to microbes since its discovery two decades ago. In this study, we aim to elucidate the activity of IL-17A in the protection against Cryptococcus neoformans, an opportunistic fungus that causes fatal meningoencephalitis among AIDS patients. For this purpose, we examined if C. neoformans infection triggers IL-17A secretion in vivo using wildtype C57BL/6 mice. In addition, an enhanced green fluorescence protein (EGFP) reporter and a knockout (KO) mouse models were used to track the source of IL-17A secretion and explore the protective function of IL-17A, respectively. Results: Our findings showed that in vivo model of C. neoformans infection demonstrated induction of abundant IL-17A secretion. By examining the lung bronchoalveolar lavage fluid (BALF), mediastinal lymph node (mLN) and spleen of the IL-17A-EGFP reporter mice, we showed that intranasal inoculation with C. neoformans promoted leukocytes lung infiltration. A large proportion (~ 50%) of the infiltrated CD4+ helper T cell population secreted EGFP, indicating vigorous TH17 activity in the C. neoformans-infected lung. The infection study in IL-17A-KO mice, on the other hand, revealed that absence of IL-17A marginally boosted fungal burden in the lung and accelerated the mouse death. Conclusion: Therefore, our data suggest that IL-17A is released predominantly from TH17 cells in vivo, which plays a supporting role in the protective immunity against C. neoformans infection.